Analysis of biomass hydrothermal liquefaction and biocrude-oil upgrading for renewable jet fuel production: The impact of reaction conditions on production costs and GHG emissions performance. (December 2017) - Tzanetis, Konstantinos F.; Posada, John A.; Ramirez, Andrea
Abstract: This paper shows a detailed analysis of a biomass HTL process by considering changes in three main reaction variables ( i.e. catalysts (water, Na2 CO3 (aq.), and Fe(aq.)), temperature (280–340 °C), and catalysts/biomass mass ratio (0–0.33 kg catalysts/kg biomass)), and by assessing their influence on the techno-economic and GHG emissions performance. This analysis is based on Aspen Plus® simulations, process economics and life-cycle GHG assessment on SimaPro (using Ecoinvent 2.2). Results showed that the lowest production cost for biocrude oil is achieved when HTL is performed at 340 °C with Fe as catalyst (450 €/tbiocrude-oil or 13.6 €/GJbiocrude-oil ). At these conditions, the biocrude oil produced has an oxygen content of 16.6 wt% and a LHV of 33.1 MJ/kgbiocrude-oil . When the hydrotreatment and hydrogen generation units are included, the total production costs was 1040 €/tupgraded-oil or 0.8 €/Lupgraded-oil . After fractionation, the estimated production cost was 1086 €/tbiojet-fuel or 25.1 €/GJbiojet-fuel . This value is twice the commercial price of fossil jet fuel. However, the allocated life cycle GHG emissions for renewable jet fuel were estimated at 13.1 kgCO2-eq ./GJbiojet-fuel, representing only 15% the GHG emission of fossil jet fuel and therefore, indicating a significant potential on GHG emission reduction. Highlights: Detailed simulation, cost estimations and GHG assessment of a biomass HTL process. Effects of main HTL variables: temperature, catalyst, and catalysts/biomass ratio. Lowest production cost of biocrude oil achieved for: HTL at 340 °C and Fe (catalyst). biojet-fuel production costs (1086 €/t or 25.1 €/GJ) are twice higher than fossil's. biojet fuel GHG emissions (13.1 kgCO2 -eq./GJ) are 15% of those from fossil's.